Durability of the Mitroflow Pericardial Prosthesis: Influence of Patient–Prosthesis Mismatch and New Anticalcification Treatment - Blasi, Stefania; Ravenni, Giacomo; Celiento, Michele; De Martino, Andrea; Milano, Aldo D.; Bortolotti, Uberto (The Thoracic and Cardiovascular Surgeon, 2020)
Background The Mitroflow pericardial bioprosthesis (MPB) has been recently associated with a high incidence of early structural failures, questioning its validity as cardiac valve substitute. We have therefore reviewed our experience with this device.Materials and Methods A total of 398 patients with a mean age of 75 ± 7 years (58% above the age of 75 years) had aortic valve replacement with a Mitroflow prosthesis (2005–2015). Most patients had calcific aortic stenosis (86%) and were in sinus rhythm (89%). Mean EuroSCORE II was 5.5 ± 6.2. Mean follow-up was 4 ± 2 years (range: 4 months to 10 years), which was 100% complete.Results Hospital mortality was 6.5%; at discharge, 25% of patients had a moderate patient–prosthesis mismatch and none had a severe mismatch. Cumulative incidence of structural valve deterioration in the entire series was 2% (95% confidence interval [CI]: 1–4) at 5 years and 7% (95% CI: 4–14) at 8 years. Significant factors influencing MPB durability were age ≤ 65 years (p < 0.001) and the presence of patient–prosthesis mismatch (p = 0.01). No cases of structural valve deterioration were observed in patients with the new prosthetic model incorporating an anticalcification treatment the first 4 years of follow-up.Conclusions The Mitroflow prosthesis has shown satisfactory results in the first decade of use. Durability appears adversely influenced by patient age and patient–prosthesis mismatch. Thus, a careful valve size selection and implantation in patients >65 years of age appears to be associated with excellent valve durability in the aortic position. Whether the new anticalcification treatment will provide a more durable prosthesis must be verified at a longer follow-up.
Keywords: aortic valve; aortic valve replacement; bioprosthesis